Assessing of Physicochemical Parameters and Seasonal Variations in the Tinau River of Palpa, Nepal - Nepali, Pit Bahadur; Rana, Hira Bahadur; Shrestha, Santoshi (Tribhuvan Journal, 2023)
The water quality and quantity parameters in lakes, rivers, marshes and lagoons are affected from both natural factors and human activities. The present study was undertaken to assess the quality of water samples with special reference to physicochemical properties of Tinau River. The water samples were collected from November 2021 to September, 2022 and analysed 17 physico-chemical parameters (Temperature, PH, dissolved oxygen, free CO2, total alkalinity, hardness, turbidity, Ammonia, Nitrogen, Chlorine, Chromium, Copper, Cyanide, Iron, Nitrate nitrogen, Phosphorus, Silica and Sulphide). The result physic-chemical parameters show that turbidity of water is with slightly basic property with PH 8, temperature between16-17°C, DO (9-10.1mg/L), Total alkalinity (65-98mg/l), Hardness (4.8-10.5mg/l), Free CO2 (3-4), Ammonia nitrate trace and other components are negative. This showed that research area are good to excellent quality water for different purposes. In addition, for the purpose of maintaining water quality, it is essential to understand specifics about many physico-chemical properties. These factors need additional study because they can induce water poisoning or chronic poisoning in aquatic animals.